Acupuncture as a Complementary Therapy for Cancer-Induced Bone Pain: A Systematic Review and Meta-Analysis - Yan, Zhaobo; MuRong, Zhimiao; Huo, Bixiu; Zhong, Huan; Yi, Chun; Liu, Mailan; Liu, Mi (Frontiers in Pain Research, 2022)
Background: Cancer-induced bone pain (CIBP) is a special type of cancer pain and lack of safe and effective treatments. Acupuncture is a potentially valuable treatment for CIBP, studies evaluating the effect of acupuncture on CIBP have been increased significantly, but the safety and efficacy of acupuncture to control CIBP remains controversial. Objective To provide the first meta-analysis to evaluate the safety and efficacy of acupuncture in CIBP management. Method Seven databases were searched from their inception through to June 1, 2022. RCTs focusing on the effectiveness of acupuncture on CIBP were included. The risk of bias was assessed by the Cochrane Collaboration’s tool for assessing risk of bias. The quality of the evidence for main outcomes were evaluate by GRADE system. Results Thirteen RCTs (with 1069 patients) were included, all studies were at high risk of bias owing to lack of blinding or other bias. Eleven studies evaluated the effectiveness of acupuncture as a complementary therapy, and showed that acupuncture plus control treatment (compared with control treatment) was connected with reduced pain intensity (MD = -1.34, 95% CI -1.74 to -0.94; Q<0.1; I2 = 98%, P<0.01). Subgroup analyses based on acupoints type partly explain the potential heterogeneity. The results also showed that acupuncture plus control treatment (compared with control treatment) was connected with relieving pain intensity, increasing the pain relief rate, reducing the frequency of breakthrough pain, shortening analgesic onset time, extending the analgesic duration, and improving quality of life. We have no sufficient evidence to prove the effectiveness of acupuncture alone. Four RCTs reported only adverse events related to opioids’ side effects. However, evidence was qualified as “very low”. Conclusion: Acupuncture has a certain effect as a complementary therapy on pain management of CIBP, which not only mitigates the pain intensity, but also improves the quality of life and reduces the incidence of opioids’ side effects, although the evidence level was very low. In the future, larger sample-size and rigorously designed RCTs are needed to provide sufficient evidence to identify the efficacy and safety of acupuncture as a treatment for CIBP.